Proposed Marketing Experiences Throughout The Integration Program Of Saudagar Laweyan To Increase Purchase Intentions - Nisrina Hanna Fakhrya; Windasari, Nila Armelia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research explores the marketing strategies and customer behavior within Saudagar Laweyan, a prominent F&B business in Surakarta, Indonesia. Despite its long-standing reputation and diverse menu offerings, Saudagar Laweyan has experienced declining sales, primarily due to changing customer behaviors and increased competition. The study focuses on understanding customer satisfaction and purchase intentions in relation to the restaurant’s servicescape quality, product innovation, and promotional activities. Qualitative and quantitative methods, including interviews with the managing director and surveys among customers, are employed to investigate these aspects. The research aims to determine the most effective marketing strategies to enhance customer purchase intentions and improve Saudagar Laweyan's overall performance in the competitive F&B sector.